Effects of Orientations on Efficiency of Energy Harvesting from Heart Motion Using Ultrathin Flexible Piezoelectric Devices. Issue 7 (6th May 2019) - Zhang, Yangyang; Lü, Chaofeng; Lu, Bingwei; Feng, Xue; Wang, Ji
Abstract: Harvesting biomechanical energy from the heart motion with flexible piezoelectric transducers to power implantable devices has attracted much attention in recent years. In vivo animal experiments have shown that the output power of flexible device depends heavily on the patching orientations. In this paper, an electromechanical model with the effects of myocardial fiber is developed to better understand the underlying mechanism of this phenomenon and therefore to choose optimal patching orientations for energy harvesting. Theoretical output voltage of the piezoelectric energy harvester under the heart motion in one cardiac cycle is calculated, and the voltage amplitudes of the harvester with varied patching orientations are compared with the experimental measurements. It is found that the output voltage amplitudes are generally the cosine function of the angle between patching orientation of the piezoelectric energy harvesters (PEHs) and the fiber orientation of the epicardium. The results may serve as a guideline to determine the optimal patching orientation of flexible PEHs mounted on surfaces of fiber structure. Abstract : Output power of piezoelectric energy harvesters mounted on heart surface depends on the patching orientations w.r.t. the myocardial fiber. An electromechanical model is developed for better understanding of this phenomenon. Results show that the output voltage amplitudes are generally the cosine function of the angle between patching orientation of the harvesters and the fiber orientation of the epicardium.